Using Multimodal Learning in Arabic Vocabulary Instruction at Islamic Elementary School - Fahmi, Nurul; Latuf, Lingkan Haifa; Fatchiatuzahro, Fatchiatuzahro (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study investigates using a multimodal learning technique in teaching Arabic vocabulary to sixth-grade primary school pupils at Madrasah Ibtidaiyah Mathlaul Anwar. Researchers employed a qualitative technique to understand better how a multimodal learning strategy is utilized to acquire Arabic. This study used both primary and secondary data. Primary data, collected directly from the source, consisted of classroom observations and in-depth interviews with the teacher and 36 sixth-grade students at Madrasah Ibtidaiyah Mathlaul Anwar. Secondary data is gathered from existing sources, including relevant literature, teaching materials, and student textbooks. The data analysis in this research uses Stevick's phenomenological method, focusing on understanding participants' subjective experiences. It involves collecting data through interviews, observations, and documents, then analyzing themes to interpret the meanings of participants' experiences. Observations and studies indicate that using multimodal learning to teach Arabic vocabulary at Madrasah Ibtidaiyah Mathlaul Anwar offers significant benefits, notably improved student interest, memory, and language competency. Presenting information through multiple modalities, rather than just text, increases student engagement and motivation. Therefore, multimodal learning can effectively enhance Arabic language instruction in elementary schools. The study recommends that teachers incorporate diverse media, especially stimulating student senses, more frequently during lessons to achieve better language teaching outcomes.